We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
62
3
avatar

 

all i know that a = 3

 Mar 31, 2019
 #1
avatar+615 
-3

Give me a second I belive you posted this before let me look BACK

 Mar 31, 2019
 #2
avatar+615 
-2

Yes you did post it but knowone helped

 

https://web2.0calc.com/questions/please-help_95973

Nickolas  Mar 31, 2019
 #3
avatar
+2

Simplify the following:
2 - (x + 1)/(x - 2) - (x - 4)/(x + 2)

Put each term in 2 - (x + 1)/(x - 2) - (x - 4)/(x + 2) over the common denominator (x - 2) (x + 2): 2 - (x + 1)/(x - 2) - (x - 4)/(x + 2) = (2 (x - 2) (x + 2))/((x - 2) (x + 2)) + ((-x - 1) (x + 2))/((x - 2) (x + 2)) + ((4 - x) (x - 2))/((x - 2) (x + 2)):
(2 (x - 2) (x + 2))/((x - 2) (x + 2)) + ((-x - 1) (x + 2))/((x - 2) (x + 2)) + ((4 - x) (x - 2))/((x - 2) (x + 2))

(2 (x - 2) (x + 2))/((x - 2) (x + 2)) + ((-x - 1) (x + 2))/((x - 2) (x + 2)) + ((4 - x) (x - 2))/((x - 2) (x + 2)) = (2 (x - 2) (x + 2) + (-x - 1) (x + 2) + (4 - x) (x - 2))/((x - 2) (x + 2)):


(2 (x - 2) (x + 2) + (-x - 1) (x + 2) + (4 - x) (x - 2))/((x - 2) (x + 2))

(x - 2) (x + 2) = (x) (x) + (x) (2) + (-2) (x) + (-2) (2) = x^2 + 2 x - 2 x - 4 = x^2 - 4:
(2 x^2 - 4 + (-x - 1) (x + 2) + (4 - x) (x - 2))/((x - 2) (x + 2))

2 (x^2 - 4) = 2 x^2 - 8:


(2 x^2 - 8 + (-x - 1) (x + 2) + (4 - x) (x - 2))/((x - 2) (x + 2))

(x + 2) (-x - 1) = (x) (-x) + (x) (-1) + (2) (-x) + (2) (-1) = -x^2 - x - 2 x - 2 = -x^2 - 3 x - 2:
(-8 + 2 x^2 + -x^2 - 3 x - 2 + (4 - x) (x - 2))/((x - 2) (x + 2))

(x - 2) (4 - x) = (x) (4) + (x) (-x) + (-2) (4) + (-2) (-x) = 4 x - x^2 - 8 + 2 x = -x^2 + 6 x - 8:
(-x^2 + 6 x - 8 + 2 x^2 - x^2 - 3 x - 8 - 2)/((x - 2) (x + 2))

 

Grouping like terms, 2 x^2 - x^2 - x^2 + 6 x - 3 x - 8 - 8 - 2 = (-3 x + 6 x) + (-8 - 2 - 8) + (2 x^2 - x^2 - x^2):
((-3 x + 6 x) + (-8 - 2 - 8) + (2 x^2 - x^2 - x^2))/((x - 2) (x + 2))

6 x - 3 x = 3 x:


(3 x + (-8 - 2 - 8) + (2 x^2 - x^2 - x^2))/((x - 2) (x + 2))

2 x^2 + (-x^2 - x^2) = 0:


(3 x + (-8 - 2 - 8))/((x - 2) (x + 2))

-8 - 2 - 8 = -18:


(3 x + -18)/((x - 2) (x + 2))

Factor 3 out of 3 x - 18:


(3 (x - 6))/((x - 2) (x + 2))=3x - 18 / x^2 - 4

a = 3      and     b=18

 Mar 31, 2019

10 Online Users